A role corporate governance and firm's environmental performance: a moderating role of institutional regulations - Akram, Farheen; Abrar-ul-haq, Muhammad; Raza, Saqlain (Universiti Utara Malaysia, 2018)
Climate change has become one of the biggest issue across the globe as most countries have been bearing the consequences of this phenomenon on a global scale. Countries have been drafting environmental regulations to help mitigate the environmental pollution caused by climate change. Therefore, the implications of environmental policies in various sectors of the economy are dependent on state regulations. The main objective of this study is to investigate the impact of corporate governance on environmental performance. Furthermore, this study examines the impact of institutional regulations on the relationship of corporate governance and firms’ environmental performance. The data was collected from the top 120 manufacturing companies that are based in Pakistan, India, China and Bangladesh. The binary logit regression methodology was employed in this study. The results indicate that the attributes of corporate governance have a positive and significant impact on green performance. In addition, the results were also positive and significant on the moderating role of institutional regulation for corporate governance and firm performance. Hence, based on the empirical findings, this study recommends strict environmental institutional regulations to further enhance environmental performance.